Molecular identification of Fusarium species isolated from transgenic insect-resistant cotton plants in Mexicali valley, Baja California - Gonzalez Soto, T.; González Mendoza, D.; Troncoso Rojas, R.; Morales Trejo, A.; Cecena Duran, C.; García López, A.; Grimaldo Juarez, O. (2015)
Cotton production in the Mexicali valley is adversely affected by wilt and root rot disease associated with Fusarium species. In the present study, we sought to isolate and identify the Fusarium species in the rhizosphere of transgenic insect-resistant cotton plants grown in the Mexicali valley. Our analyses isolated four native fungi from the rhizosphere of cotton plants, namely, T-ICA01, T-ICA03, T-ICA04, and T-ICA08. These fungal isolates were categorized as belonging to Fusarium solani using their phenotypic characteristics and ITS region sequence data. Examination of the infection index showed that T-ICA03 and T-ICA04 caused systemic colonization (90%) of seeds followed by the occurrence of radicle and coleoptile decay. In contrast, T-ICA08 strain was less pathogenic against seed tissues (40%) in comparison to the other strains isolated. Our study showed that in transgenic insect-resistant cotton the disease “Fusarium wilt” is caused by the fungus, F. solani. Future studies are necessary to characterize the F. solani populations to determine whether phenological stages might influence the genetic diversity of the fungal populations present.